2017
DOI: 10.18632/oncotarget.21456
|View full text |Cite
|
Sign up to set email alerts
|

Low expression of SerpinB2 is associated with reduced survival in lung adenocarcinomas

Abstract: In summary, low expression of SerpinB2 in lung adenocarcinomas was an independent prognostic factor. In contrast to findings by others, we found no impact of L1CAM on survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 53 publications
1
12
0
1
Order By: Relevance
“…Increased SERPINB2 expression has been reported in various inflammatory or autoimmune diseases, including psoriasis, asthma, preeclampsia and lupus erythematosus . In addition, increased SERPINB2 has been previously shown to be a potential biomarker in discriminating non‐allergic asthma and its severity while reduced expression of SERPINB2 was an independent prognostic marker in lung adenocarcinomas associated with reduced survival . Our study suggests that increased SERPINB2 expression is associated with more severe psoriasis.…”
Section: Discussionsupporting
confidence: 59%
“…Increased SERPINB2 expression has been reported in various inflammatory or autoimmune diseases, including psoriasis, asthma, preeclampsia and lupus erythematosus . In addition, increased SERPINB2 has been previously shown to be a potential biomarker in discriminating non‐allergic asthma and its severity while reduced expression of SERPINB2 was an independent prognostic marker in lung adenocarcinomas associated with reduced survival . Our study suggests that increased SERPINB2 expression is associated with more severe psoriasis.…”
Section: Discussionsupporting
confidence: 59%
“…Loss of expression of SerpinB2 was, however, shown to be associated with the activation of tumor growth and metastasis in several cancer types, including BC 3234 . Expression levels of SerpinB2 was also shown to correlate negatively with survival of patients with lung carcinomas 35 . Also, downregulation of SerpinB2 was found to contribute to chemoresistance in head and neck carcinomas 36 .…”
Section: Discussionmentioning
confidence: 94%
“…It was reported that the elevated expression of SPB2 resulted in a poor survival of bladder cancer patients 27 , or patients diagnosed with esophageal squamous cell carcinoma 28 . However, reduced expression of SPB2 also leads to reduced survival rate of patients suffering from breast 29–31 or pancreatic cancer 32 . In this study we demonstrate that upon UV irradiation SPB2 mRNA level is highly increased in cell types originated from skin tissue.…”
Section: Resultsmentioning
confidence: 99%